2022
DOI: 10.17305/bjbms.2022.7545
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of HDL-C on long-term mortality in patients with COVID-19 pneumonia in the Turkish population: A potential mechanism for population differences

Abstract: Coronavirus disease 2019 (COVID-19) is diagnosed by the evidence of the presence of multiple phenotypes, including thrombosis, inflammation, and alveolar and myocardial damage, which can cause severe illness and mortality. High-density lipoprotein cholesterol (HDL-C) has pleiotropic properties, including anti-inflammatory, anti-infectious, antithrombotic, and endothelial cell protective effects. The aim of this study was to investigate the HDL-C levels and one-year mortality after the first wave of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…This suggests that a more pronounced dyslipidemia may result from a stronger in ammatory response. Our study found that non-surviving COVID-19 patients exhibited a robust in ammatory response, as indicated by higher levels of WBC, neutrophil count, and CRP, which is consistent with previous studies (7,13,15,(17)(18)(19). In sepsis patients, TC and HDL decreased during the acute phase and slowly increased within 28 days (20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that a more pronounced dyslipidemia may result from a stronger in ammatory response. Our study found that non-surviving COVID-19 patients exhibited a robust in ammatory response, as indicated by higher levels of WBC, neutrophil count, and CRP, which is consistent with previous studies (7,13,15,(17)(18)(19). In sepsis patients, TC and HDL decreased during the acute phase and slowly increased within 28 days (20).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, HDL has been identi ed as a predictor for one-year mortality after COVID-19 (15). Consequently, it appears that the lipid pro le may play a crucial role in determining the prognosis of patients with COVID-19, both in the long-term and the short-term.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly decreased HDL levels in patients with COVID-19 were correlated with both disease severity and mortality [ 11 , 20 , 21 ]. A study from Turkey even considers it a good predictor of one-year mortality in patients with COVID-19 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stewart et al 25 associated low HDL-c levels with fatal COVID-19 courses, while Ghoreshi et al 26 suggested that the cytokine milieu in COVID-19 could lead to decreased HDL-c levels. Baycan et al 27 discussed the long-term mortality implications of HDL-c levels in COVID-19 patients, highlighting its prognostic significance.…”
Section: Introductionmentioning
confidence: 99%